Abstract art painting : expressions in mixed media - Stewart, Debora, frey50 (Cincinnati, Ohio North Light Books, 2015)
"In Abstract art painting, you will enter a realm of tactile, intuitive excitement, combining pastel and acrylic to achieve results as unique as you are. You'll learn how to explore the use of color theory in abstraction and to use underpainting to bring structure and depth to you art. In addition you'll begin to understand how to work in a series and how this can help you develop your own personal style"--Back cover.
Includes summary and index
Keywords: Painting, Abstract -- Technique; Mixed media (Art) -- Technique